Plataforma de encapsulamento de microrganismos em matriz PVA para uso na agricultura como inoculante microbiano - Lodi, Ludimila Araújo (Universidade Federal de São Carlos, 2024)
This study aimed to develop novel microbial inoculants for the encapsulation of Bacillus megaterium. Films and microparticles were prepared from polyvinyl alcohol (PVA)-based formulations using casting, emulsion, and spray drying techniques. The materials that best protected the encapsulated bacteria from stresses such as heat, UV light, and agrochemicals were applied in different ways: as a coating on soybean seeds (films), in soils with high salinity (emulsion microparticles), and as a solid inoculant in greenhouse experiments using soybeans with a model plant (spray-dried microparticles). Initially, biodegradable PVA films were developed that were cross-linked with citric acid. At a concentration of 30% (w/v), citric acid reduced the swelling and solubility of the films, increased their resistance to degradation, and influenced the controlled release of the encapsulated bacteria. The films promoted similar germination rates of soybean seeds treated with commercial polymers and outperformed the untreated seeds. This proves their application potential. Microparticles based on PVA/cationic starch were developed using a simple crosslinking/emulsion method, and the effect of the cross-linking agents citric acid (CA), sodium trimetaphosphate (STMP), and bentonite as surface modifiers was investigated. The presence of STMP/bentonite increased the estimated shelf life of this formulation. In high salinity soil tests (200 mM), these microparticles provided a favorable environment for bacterial development, with final cell viability higher than that of the inoculum, even after 7 days of high salinity. Finally, zinc oxide (ZnO) was added to the PVA/cationic starch formulation to produce microparticles by spray drying. The presence of zinc and bacteria in the formulation significantly promoted the production of biomass in the aerial and root zones of soybean plants and enhanced the uptake of phosphorus and zinc when applied as a solid inoculant in greenhouse tests. The results show that the proposed formulations and methods to produce novel microbial inoculants are promising strategies for efficient agricultural applications.
Microorganism encapsulation platform in PVA matrix for use in agriculture as a microbial inoculant
Keywords: Bacillus; Biofertilizante; Amido catiônico; Ácido cítrico; Trimetafosfato de sódio; Zinco; Estresses; Emulsão; Spray-dryer; Biofertilizers; Cationic starch; Citric acid; Sodium trimetaphosphate; Zinc; Stress; Emulsion; Spray dryer; ENGENHARIAS::ENGENHARIA QUIMICA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA